Pemberdayaan UMKM Berkah Jaya Bulungan Melalui Teknologi Tepat Guna dan Pemasaran Digital - Rusdy Setiawan; Irawati Irawati; Ardiansyah Ardiansyah; Nabilah Febrianty; Felisya Shandy Aulia (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The Community Service Program (PKM) under the Community Partnership Empowerment (BIMA) scheme aims to increase the productivity, managerial capacity, and competitiveness of Berkah Jaya MSMEs in Bulungan Regency, North Kalimantan Province through the integrated application of appropriate technology and strengthening of human resource capacity. The program is implemented through five stages: socialization, training, technology implementation, mentoring and evaluation, and program sustainability. Hard technology in the form of a spice grinder, a meatball printing machine, a 7-liter mixer, and a Rok Presso Smartshot were handed over through BASTA. Soft technology includes digital marketing training, digital financial bookkeeping, and halal certification. The results of the pre-test and post-test evaluations showed a statistically significant increase in knowledge (pre-test M=50.00; post-test M=90.00; Z=−2.014; p=0.022; Wilcoxon Signed-Rank Test, one-tailed). All participants successfully created business Instagram accounts and registered their business locations on Google Maps after the training. Production efficiency increased significantly through the use of the meatball printing machine